1996
DOI: 10.1093/intqhc/8.5.447
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Meeting Patients' Information Needs and their Satisfaction with Hospital Care and General Health Status Outcomes

Abstract: The results suggest that providers of care should ensure that they meet the information needs of patients with specific conditions because patients' perceptions of both quality of care and quality of life are associated with the clinicians' ability to transfer key information to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 15 publications
8
75
0
6
Order By: Relevance
“…Larson et al found that physician ability to meet patient's information needs was positively associated with patient satisfaction. 29 Similarly, Tarrant et al found that patient's trust in a physician improved with increasing communication, interpersonal care, and knowledge of the patient. Interestingly, continuity, ie.…”
Section: Discussionmentioning
confidence: 97%
“…Larson et al found that physician ability to meet patient's information needs was positively associated with patient satisfaction. 29 Similarly, Tarrant et al found that patient's trust in a physician improved with increasing communication, interpersonal care, and knowledge of the patient. Interestingly, continuity, ie.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that 54 of 72 (75%) answering patients were satisfied with the information they received about the postponement/ cancellation (Ivarsson et al 2002). In 1996, Larson et al (1996 showed a clear connection between adequate information and the patient's satisfaction with medical treatment.…”
Section: Perceptions Of Informationmentioning
confidence: 99%
“…Larson et al (1996) have also shown that meeting information needs is positively and significantly associated with patient satisfaction with hospital treatment.…”
Section: Introductionmentioning
confidence: 91%